Pengaruh Fasilitas dan Kualitas Pelayanan terhadap Kepuasan Pasien - Angga Adi Saputra (Universitas Islam Kadiri, 2018)
This study aims to analyze the effect of facilities and service quality on patient satisfaction at Kartika Kediri Inpatient Clinic.Population in this research is patient of Kawatika Kediri Inpatient Clinic. Sampling technique used simple random sampling with 127 respondents. This study uses multiple linear regression analysis tools. The hypothesis was tested by t test and F test. Test results showed that facility (X1) and service quality (X2) had significant influence on patient satisfaction (Y). Indicated by F arithmetic of 79.225 is greater when compared with F table 3.07. The t test shows that facility (X1) and service quality (X2) variables have significant influence on patient satisfaction. This is shown from the value of t arithmetic for variael X1 of 5.128 and t count variable X2 of 5.469 larger than t table 1.97928. Hypothesis test shows that the correlation coefficient (R) is 56.1%. This means that the relationship between the variable facilities and service quality with patient satisfaction is strong enough. Results of multiple linear regression analysis with the equation Y = 6.389 + 0.418 X1 + 413 X2.